2020
DOI: 10.1021/acs.biomac.9b01610
|View full text |Cite
|
Sign up to set email alerts
|

Polyplexes Are Endocytosed by and Trafficked within Filopodia

Abstract: The improvement of nonviral gene therapies relies to a large extent on understanding many fundamental physical and biological properties of these systems. This includes interactions of synthetic delivery systems with the cell and mechanisms of trafficking delivery vehicles, which remain poorly understood on both the extra- and intracellular levels. In this study, the mechanisms of cellular internalization and trafficking of polymer-based nanoparticle complexes consisting of polycations and nucleic acids, terme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 106 publications
2
22
0
Order By: Relevance
“…The cationic nature of the nanoaggregates creates favorable electrostatic interactions with the negatively charged cellular membrane, inducing uptake. The route of uptake observed here is similar to that observed by Reineke et al, 54 where polyplexes were uptaken into cells via the filopodia, then trafficked into the lamellipodia. The confocal images (Figure 5(A)) indicate that the cationic nanoparticles are being up‐taken via endocytosis by the filopodia, the actin projections that extend from the surface of the HEK cells.…”
Section: Resultssupporting
confidence: 88%
“…The cationic nature of the nanoaggregates creates favorable electrostatic interactions with the negatively charged cellular membrane, inducing uptake. The route of uptake observed here is similar to that observed by Reineke et al, 54 where polyplexes were uptaken into cells via the filopodia, then trafficked into the lamellipodia. The confocal images (Figure 5(A)) indicate that the cationic nanoparticles are being up‐taken via endocytosis by the filopodia, the actin projections that extend from the surface of the HEK cells.…”
Section: Resultssupporting
confidence: 88%
“…The cationic surface charge of TRPZ-bisMPA NPs leads to apparent cellular uptake via electrostatic interactions with anionic cell membranes. Similar results have been observed with other dendrimer-based NPs modified with anime groups (Morris et al, 2017;Ray et al, 2018;Ingle et al, 2020). Likely owing to the polar groups on the MPA dendron, TRPZ fluorescence is observed throughout the interior of the lysosome (Figure 4D).…”
Section: Photophysical Propertiessupporting
confidence: 88%
“…Outside PEI, Reineke and coworkers tracked the filopodia-driven transport of polyplexes formulated from the cationic glycopolymer Glycofect and concluded that these complexes were trafficked over long distances (13 μm) along filopodial projections at a velocity from 0.003 to 0.07 μm•s −1 . 255 There is debate about the timing of DNA release by polycations, and it is unclear if polyplexes outside of endosomes are efficiently trafficked. There is evidence, however, that some naked plasmids (i.e., plasmids uncomplexed from the polycation) can utilize intracellular machinery in the cytoplasm to complete the race to the nucleus and allow for nuclear uptake.…”
Section: Intracellular Barriersmentioning
confidence: 99%